Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4ra09214g
|View full text |Cite
|
Sign up to set email alerts
|

Production of novel biodiesel from transesterification over KF-modified Ca–Al hydrotalcite catalyst

Abstract: A series of KF-modified Ca-Al hydrotalcite (xKF/HTL-M) solid base catalysts was prepared in methanol, and characterized by thermogravimetry analysis (TG-DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM) and carbon dioxide temperature-programmed desorption (CO 2 -TPD). The catalytic activity was investigated in the transesterification of ethylene glycol monomethyl ether (EGME) with methyl laurate (ML) to produce a novel biodiesel of ethylene glycol monomethyl ether monolaurate (EGMEML). The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…00-027-0431) was observed. When the loading amount of KF was 40 wt%, CaF 2 and K 2 O diffraction intensity remained approximately constant, which may have resulted from excess KF covering the active sites, and dispersing well on the catalyst surface, so that the characteristic peaks of KF were not obviously emerged [33][34][35].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…00-027-0431) was observed. When the loading amount of KF was 40 wt%, CaF 2 and K 2 O diffraction intensity remained approximately constant, which may have resulted from excess KF covering the active sites, and dispersing well on the catalyst surface, so that the characteristic peaks of KF were not obviously emerged [33][34][35].…”
Section: Resultsmentioning
confidence: 93%
“…3a), for basicity and basic strength play a significant role [27] in transesterification. Two desorption peaks between 470-610°C and 610-730°C were observed for Ca/MMT and KCa/MMT-10, the former is due to the interaction of CO 2 with the moderate basic sites [31][32][33]; the latter ascribes to decomposition of the structural carbonate [36,37]. The structural carbonate might be generated during a long time period or impregnation process [37], whereas only one desorption peak between 550 and 700°C was found from that of KCa/MMT-20, 30 and 40, which is attributable to strong basic sites [38].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the process would need more power consumption for adequate stirring. Thus, the catalyst amount of 5 % is expected to be optimum in this catalytic reaction system ,…”
Section: Resultsmentioning
confidence: 99%
“…In these works, the mass ratio of KF was 1:1, with higher methanol/oil molar ratio 12:1. Additionally, it has been reported that this family of materials shows great stability after many reuse cycles in the transesterification reaction [28][29][30].…”
Section: Introductionmentioning
confidence: 99%